Polarization Optics in Telecommunications - Damask, Jay N. (Springer Series in Optical Sciences,, 2005)
The strong investments into optical telecommunications in the late 1990s resulted in a wealth of new research, techniques, component designs, and understanding of polarization effects in fiber. Polarization Optics in Telecommunications brings together recent advances in the field to create a standard, practical reference for component designers and optical fiber communication engineers. Beginning with a sound foundation in electromagnetism, the author offers a dissertation of the spin-vector formalism of polarization and the interaction of light with media. Applications discussed include optical isolators, optical circulators, fiber collimators, and a variety of applied waveplate and prism combinations. Also included in an extended discussion of polarization-mode dispersion (PMD) and polarization-dependent loss (PDL), their representation, behavior, statistical properties, and measurement. This book draws extensively from the technical and patent literature and is an up-to-date reference for researchers and component designers in industry and academia.